Toxicological evaluation of protein-enriched coconut residue flour using fertile chick embryo - Contreras, Oliver J. (1994)
Microbial biomass proteins (MBPs) provide nutritious foods for nutritionally-deficient individuals. These MBPs are derived from microbial growth on food wastes and byproducts, an example of which is the protein enriched coconut residue flour (PECRF) using solid substrate fermentation by a strain of the mold Rhizopus oligosporus. By the nature of its preparation and its being a novelty food, toxicological assessment using fertile chick embryo bioassay is imperative prior to consideration for human consumption. A total of 495 fertile chick embryos were used for the study. Inoculation of oil-soluble and water soluble extracts of PECRF and CRF were performed with 18 chick embryos per treatment. The embryos were injected, each with 0.1 ml of extract on the fifth day of incubation at 38.9°C, 63% RH reincubated for four days and candled for surviving specimens. Placebo and uninoculated controls were also treated for comparison. Exploratory and confirmatory tests were done to total four experimental runs. Results show that the 43.66% relative toxicity of PERF, assuming the same amount of extract exposures in the body, is 20.50% more than the unfermented CRF substrate. Toxicity was evaluated to have been caused by inhibitory substances developed during the fermentation process and those elaborated by the MBPs' natural microbial flora.